Underwater sound emission as part of an antipredator mechanism in Ceratophrys cranwelli tadpoles. (12th May 2013) - Salgado Costa, Carolina; Chuliver Pereyra, Mariana; Alcalde, Leandro; Herrera, Raúl; Trudeau, Vance L.; Natale, Guillermo S.
Abstract We report the emission of underwater sounds in the tadpoles of a second member of the family Ceratophryidae, Ceratophrys cranwelli. These tadpoles produce a short metallic‐like sound, which consists of short trains of pulses at Gosner stages 25, 28, and 37. Experiment I was designed to record underwater sounds and their characteristics. Experiment II was designed to test: (i) if at higher densities (total number of tadpoles/L) but fixed predator–prey proportions C. cranwelli larvae are cannibalistic, (ii) if cannibalism increases at higher proportions of predators at a fixed density, and (iii) if tadpoles display a mechanism of intraspecific recognition that may diminish the frequency of cannibalism. Each treatment combines larvae of C. cranwelli (predator) with those of Rhinella arenarum (prey). The number of live and dead individuals was recorded during 72 h, and the following variables were calculated: time to eat the first and second prey, time without eating, time to eat a congener, and number of events of cannibalism. The results indicate that relative predator–prey availability affects the frequency of predation between conspecifics. We consider that an antipredator mechanism exists in C. cranwelli tadpoles and that the underwater sound is part of it.